Connection in Joints for Thin-Walled Steel Sections and Sheeting - Othuman Mydin, M.A. (Eftimie Murgu University of Resita, 2014)
Thin-walled cold-formed members are thin, this will give rise to behavioural phenomena, which are not usually encountered in the more familiar hot-rolled sections. When compared to hot-rolled steel sections, cold-formed thin-walled steel sections are more likely to fail in local buckling, distortional buckling, various global buckling and shear buckling. This paper will discuss types of connection in Jjoints for coldformed thin-walled sections and steel sheeting. Bolts, screws, blind rivets or cartridge fired pins are commonly used in joints for coldformed thin-walled sections or steel sheet connections. Fasteners in light gauge steel tend to be relatively less stiff than their counterparts in heavier construction so that connection flexibility can be significant in certain assemblies. Furthermore, as in any load-bearing structure, it is important that connections are not brittle and this implies that there should be adequate deformation capacity.